On two new species of Nannopus Brady, 1880 (Copepoda: Harpacticoida: Nannopodidae) from intertidal mudflats of the Korean west coast (Yellow Sea) - Vakati, Vinod; Lee, Wonchoel (Zootaxa, 2021)
Two new species in the genus Nannopus Brady, 1880 (Copepoda: Harpacticoida) from intertidal mudflats of the Yellow Sea along the Korean peninsula, Nannopus cylindricus sp. nov. and N. robustus sp. nov., are described. Nannopus cylindricus belongs to the group of Nannopus species with seven elements on P4 exp-3. Within this group, it is closest to a cryptic species complex related to N. ganghwaensis Vakati, Kihara & Lee, 2016 based on an inflated caudal seta IV. However, N. cylindricus differs from the other species in this complex with respect to caudal seta V (inflated and heavily cylindrical at its base in N. cylindricus, inflated only in the N. ganghwaensis cryptic complex). Nannopus robustus belongs to the group of species displaying two setae on P2 enp-2. Within this group, N. robustus is closely related to N. serratus Vakati & Lee, 2017 based on the presence of one endopodal naked seta arising from a stem-like protrusion on the mandibular palp. However, N. robustus can be distinguished from N. serratus based on the following characters: outermost distal spine on P2 exp-3 (extremely strong, smooth and recurved in N. robustus, moderately strong, denticulate and normal-shaped in N. serratus, and spine 1.6 times as long in N. robustus as in N. serratus), P2 exp-2 inner seta (absent in N. robustus, present in N. serratus), shape of caudal seta V (anterior part distinctly cylindrical in N. robustus, normal-shaped in N. serratus), and ornamentation of caudal seta VI (naked in N. robustus, pinnate in N. serratus). An updated key to the 17 valid species of Nannopus is provided.